Modeling of gas fuel requirements in food service facilities - Jedlikowski, Andrzej; Englart, Sebastian; Skrzycki, Maciej (Instal, 2022)
The paper characterizes the activities of food service and mass caterers in Poland. Calculation methods are described to determine the gas requirements for this type of facility. Special attention was paid to the frequency of gas appliances used to prepare food for consumers. Problems arise from the inability to include simultaneity coefficients when determining the design gas flow rate. An original mathematical model has been developed that considers the consumption of gaseous fuel during the preparation of dishes in a food service facility. Based on the model, a computer program needed for numerical simulations was written. The model was then validated using measurement data obtained from the mass catering facility. Furthermore, the gas flow rate was estimated using calculation methods available in the literature. The simulation results obtained were compared with the measurement results. The high level of compliance of the model has yielded a wealth of relevant information. Failure to include simultaneity coefficients leads to elevated values of the hourly gas flow rate. Standard operation of gas appliances sometimes forces the need to use a lower gas burner flame. Daily gas consumption is subject to significant fluctuations due to the varying cooking times of meals for consumers. In the case under review, it was observed that simultaneity coefficients for the use of gas appliances in the range of 0.4-0.6 must be considered. Accurate determination of the reduction value of the design gas demand requires further research and numerical simulations of the operation of food service facilities.
Keywords: gas appliances; mathematical model; design gas flow rate